Why the Chosen Ones May Not Always Be the Best Leaders: Criteria for Captain Selection as Predictors of Leadership Quality and Acceptance - Butalia, Radhika; Fransen, Katrien; Coffee, Pete; Laenens, Jolien; Boen, Filip (Frontiers in Psychology, 2021)
There seems to be some initial evidence that team captains are selected based on non-leadership factors such as team tenure, technical abilities, being the daughter of the club president, or playing position. This is concerning given that players expect their ideal team captain to have superior motivational and social skills. Adding to this literature on captain selection the present study investigated the relationships between the reasons for which team captains are selected and their (a) perceived leadership quality and (b) perceived acceptance. To accomplish this, we recruited 450 coaches and 198 players from Flemish football and volleyball teams. Participants evaluated 41 reasons on the extent to which they played a role in the selection of their team captain. Additionally, participants rated their team captain’s leadership quality and acceptance. The results consistently indicated that captains who were selected for having good motivational and social competencies were given higher ratings on perceived leadership quality and acceptance by participants. In conclusion, athletes who are motivated, good at motivating others and have superior social skills tend to be better suited for captaincy than those selected based on non-leadership factors.